Microbiota in Dung and Milk Differ Between Organic and Conventional Dairy Farms - Gomes, Sofia I. F.; van Bodegom, Peter M.; van Agtmaal, Maaike; Soudzilovskaia, Nadejda A.; Bestman, Monique; Duijm, Elza; Speksnijder, Arjen; van Eekeren, Nick (Frontiers in Microbiology, 2020)
Organic farming is increasingly promoted as a means to reduce the environmental impact of artificial fertilizers, pesticides, herbicides and antibiotics in conventional dairy systems. These factors potentially affect the microbial communities of the production stages (soil, silage, dung and milk) of the entire farm cycle. However, understanding whether the microbiota representative of different production stages reflect different agricultural practices – such as conventional vs. organic farming – is unknown. Furthermore, the translocation of the microbial community across production stages is scarcely studied. We sequenced the microbial communities of soil, silage, dung and milk samples from organic and conventional dairy farms in the Netherlands. We found that community structure of soil fungi and bacteria significantly differed among soil types, but not between organic vs conventional farming systems. The microbial communities of silage also did not differ among conventional and organic systems. Nevertheless, the dung microbiota of cows, and the fungal communities in the milk were significantly structured by agricultural practice. We conclude that, while the production stages of dairy farms seem to be disconnected in terms of microbial transfer, certain practices specific of each agricultural system, such as the content of diet and the use of antibiotics, are potential drivers of shifts in the cow’s microbiota, including the milk produced. This may reflect differences in farm animal health and quality of dairy products depending on farming practices.